SYNTAX OF SPATIAL PATTERN OF INFORMAL SETTLEMENT AREA OF SENTRA TAHU CIBUNTU, BANDUNG - Dwi Kustianingrum, Dwi; Haerdy, Ratu Sonya Mentari (Border: Jurnal Arsitektur, 2023)
Sentra Tahu Cibuntu, a tofu supplier industry in Bandung Raya, is categorized as an informal settlement because it formed spontaneously due to national road infrastructure development in Bandung City. The designation of an ordinary settlement as a center positively impacts the city's economic growth. On the other hand, the high demand for housing for tofu makers became a new problem that resulted in an increasingly unplanned settlement growth pattern. Spatial patterns in informal settlements need to be identified as a benchmark for estimating the direction of settlement development in the future. Both designers and policymakers can determine the design strategy of the area to improve the quality of informal settlements. This research uses the space syntax approach to analyze integration on the Sentra Tahu Cibuntu axial map. Primary data was obtained through field observations combined with mapping from satellite imagery. The mapping data is processed using DepthMapX software to produce an axial map that shows the integration value, which describes the real setting. The results of the syntactic analysis are combined with the results of field observations to obtain an overview of building functions, activities, and environmental characteristics. The lower integration value is interpreted as low accessibility to residential areas, so residents have high vulnerability to security and safety, limited infrastructure, limited social activities, and low quality of occupant health. Designers can use the results of these findings as a consideration in designing inclusive and sustainable residential areas through innovative designs.